Moho depth variations over the Maldive Ridge and adjoining Arabian and Central Indian Basins, Western Indian Ocean, from three dimensional inversion of gravity anomalies - Kunnummal, Priyesh; Anand, S.P.; Haritha, C.; Rao, P. Rama (My University, 2018)
Analysis of high resolution satellite derived free air gravity data has been undertaken in the Greater Maldive Ridge (GMR) (Maldive Ridge, Deep Sea Channel, northern limit of Chagos Bank) segment of the Chagos Laccadive Ridge and the adjoining Arabian and Central Indian Basins. A Complete Bouguer Anomaly (CBA) map was generated from the Indian Ocean Geoidal Low removed Free Air Gravity (hereinafter referred to as “FAG-IOGL”) data by incorporating Bullard A, B and C corrections. Using the Parker method, Moho topography was initially computed by inverting the CBA data. From the CBA the Mantle Residual Gravity Anomalies (MRGA) were computed by incorporating gravity effects of sediments and lithospheric temperature and pressure induced anomalies. Further, the MRGA was inverted to get Moho undulations from which the crustal thickness was also estimated. It was found that incorporating the lithospheric thermal and pressure anomaly correction has provided substantial improvement in the computed Moho depths especially in the oceanic areas. But along the GMR, there was not much variation in the Moho thickness computed with and without the thermal and pressure gravity correction implying that the crustal thickness of the ridge does not depend on the oceanic isochrones used for the thermal corrections. The estimated Moho depths in the study area ranges from 7 km to 28 km and the crustal thickness from 2 km to 27 km. The Moho depths are shallower in regions closer to Central Indian Ridge in the Arabian Basin i.e., the region to the west of the GMR is thinner compared to the region in the east (Central Indian Basin). The thickest crust and the deepest Moho are found below the N-S trending GMR segment of the Chagos-Laccadive Ridge. Along the GMR the crustal thickness decreases from north to south with thickness of 27 km below the Maldives Ridge reducing to ∼9 km at 3°S and further increasing towards Chagos Bank. Even though there are similarities in crustal thickness between Maldive Ridge and other regions like Mascarene Plateau which was recently interpreted as underlain by continental crust, much more geoscientific work including drilling has to be undertaken to finally confirm the exact nature of the ridge.
Keywords: Geodynamic evolution; Cuddapah basin; Eastern Ghats Belt; Potential field anomalies; Crustal seismic structure; India-Antarctica collision